A vulnerabilidade das economias europeias ante a crise financeira internacional: um estudo para países selecionados - Nunes Neto, Afonso de Deus (2013)
Whereas the decisive performance of the public sector in the economies affected by the international financial crisis of 2008, this thesis investigates how the key European economies lead his tax policy to establish a measure of vulnerability of the Euro Area to adverse shocks such as the recent crisis. Investigates further, the functions of reaction estimated tax for eight of the main European economies and for the Euro area as a whole and the negligence of the monetary authorities of these countries in relation to the generation of primary surplus ahead to possible increases in public debt. This situation worsens in times of crisis and exposes the economies on negative impacts due to the limited ability of the public sector to conduct counter-cyclical policies able to reverse the recession, promoting the increase in the number of jobs and stimulating the growth of production.